Bariatric surgery versus community weight management intervention for idiopathic intracranial hypertension: a randomised controlled trial. Issue 6 (27th May 2022) - Mollan, Susan; Mitchell, James; Ottridge, Ryan; Aguiar, Magda; Yiangou, Andreas; torovic, Zerin Alimajs-; Cartwright, David; Grech, Olivia; ,; Sinclair, Alex J
Abstract : Objective: The IIH weight trial (IIH: WT) aimed to compare the efficacy of bariatric surgery with a community weight management intervention (CWI) in active IIH. Methods: This was a five-year randomized control trial which enrolled participants between March 1, 2014 and May 25, 2017 at five NHS hospitals in the United Kingdom. Participants with active IIH and body mass index (BMI) ≥35kg/m2 were screened. The primary outcome was change in intracranial pressure (ICP) measured by lumbar puncture (LP) opening pressure (OP) at 12 months. Results: Sixty-six women were randomised (mean age, 32 years). ICP was significantly lower in the bariatric surgery arm at 12 months (adjusted mean difference -6.00cm cerebrospinal fluid [CSF] 95% confidence interval [CI] -9.5 to -2.4]; p= 0.001) and at 24 months (adjusted mean difference -8.2cmCSF [95% CI, -12.2 to -4.2]; p< 0.001) compared with the CWI arm. Weight was significantly lower in the bariatric surgery arm at 12 months (adjusted mean difference -21.4Kg 95% CI, -32.1 to -10.7]; p< 0.001) and at 24 months (adjusted mean difference -26.6kg [95% CI, -37.5 to -15.7]; p< 0.001) compared with the CWI arm. Quality of life (SF36, physical component score) improved significantly at 12 and 24 months (adjusted mean dif- ference p=.043; p=.006, respectively). Conclusions and Relevance: In this study of women with active IIH and a BMI ≥35kg/m2, bariatric surgery was superior to a CWI in lowering ICP. soozmollan@doctors.org.uk